2011
DOI: 10.1111/j.1600-0668.2011.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of airborne cockroach allergen in New York City apartments

Abstract: We designed and tested a sampling and analysis system for quantitative measurement of airborne cockroach allergen with sufficient sensitivity for residential exposure assessment. Integrated 1-week airborne particle samples were collected at 10–15 LPM in 19 New York City apartments in which an asthmatic child who was allergic to cockroach allergen resided. Four simultaneous air samples were collected in each home: at heights of 0.3 and 1 m in the child's bedroom and in the kitchen. Extracts of air samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…One of the studies in this review suggests that air sampling deserves another look. Longer sampling times and lower flow rates can lead to recovery of cockroach allergen in air [8]; however, this might only hold for those homes (and possibly schools) where there are high concentrations of cockroach allergen in reservoir dust. Only by examining where the biologically-relevant exposures to cockroach allergens occur, will allergen avoidance strategies achieve success.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the studies in this review suggests that air sampling deserves another look. Longer sampling times and lower flow rates can lead to recovery of cockroach allergen in air [8]; however, this might only hold for those homes (and possibly schools) where there are high concentrations of cockroach allergen in reservoir dust. Only by examining where the biologically-relevant exposures to cockroach allergens occur, will allergen avoidance strategies achieve success.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7], few studies included air sampling of cockroach allergen in their exposure assessment protocols. Esposito et al [8] reported that that not only could airborne cockroach allergen be detected in homes with cockroaches, but that it could be measured using a relatively simple technique that is often used for other particulate matter (PM) sampling. In this study, children with asthma living in low-income apartments in New York City (NYC) participated in an allergen avoidance study.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular structures of Bla g 1 and Per a 1 consist of tandem repeats of approximately 100 amino acids, whereas Bla g 2 is a globular protein belonging to the family of aspartic proteases [28, 110, 111]. Bla g 1 and Bla g 2 in particular, once thought to be carried mainly on larger particles of greater than 10 μm [53•, 107–109]and thus primarily found in settled dust, have more recently been studied in air sampling with the conclusion that they also exist on smaller particles and are often airborne, so that kitchen and bedroom exposures are actually highly correlated [112] – a particularly important finding from an exposure assessment perspective [106]. …”
Section: Bedroom Allergen Exposuresmentioning
confidence: 99%
“…These include airborne indoor allergens from pets, house dust mites, and cockroaches [1, 6]. Bla g2 from the German cockroach ( Blattella germanica ) is among these allergens and thought to be an important risk factor in the development and/or exacerbation of atopic asthma [6, 9].…”
Section: Introductionmentioning
confidence: 99%
“…These include airborne indoor allergens from pets, house dust mites, and cockroaches [1, 6]. Bla g2 from the German cockroach ( Blattella germanica ) is among these allergens and thought to be an important risk factor in the development and/or exacerbation of atopic asthma [6, 9]. Bla g2 is detected in 87–93% of air samples in the bedroom and kitchen often in concentrations of Bla g2 that approach the threshold for sensitization in homes of children with asthma [6].…”
Section: Introductionmentioning
confidence: 99%